2017
DOI: 10.1093/ntr/ntw329
|View full text |Cite
|
Sign up to set email alerts
|

Waterpipe Promotion and Use on Instagram: #Hookah

Abstract: In the US Instagram posts with the hashtag #hookah regularly depicted waterpipe use in conjunction with alcohol use. Instagram's focus on images facilitates picture-based advertising where hookah lounges promote drink specials at the same time nightclubs promote waterpipe specials. Instagram users often document the variety of shapes, sizes, and styles, of waterpipes, suggesting users take pride in their purchases and like to show their customized, and often times elaborate, waterpipes to their followers. Inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 21 publications
3
71
1
2
Order By: Relevance
“…The tobacco product or promotion theme constituted 17.69% of images in this study, while a previous study on hookah similarly reported that 18% of images showed promotional materials [ 10 ]. Among all images in our study, 5.49% showed alcohol, which is less than in prior work, where 31% of all hookah-related images showed or referenced alcohol use [ 10 ]. This finding suggests that little cigar and cigarillo use may not co-occur as often as hookah with alcohol consumption.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The tobacco product or promotion theme constituted 17.69% of images in this study, while a previous study on hookah similarly reported that 18% of images showed promotional materials [ 10 ]. Among all images in our study, 5.49% showed alcohol, which is less than in prior work, where 31% of all hookah-related images showed or referenced alcohol use [ 10 ]. This finding suggests that little cigar and cigarillo use may not co-occur as often as hookah with alcohol consumption.…”
Section: Discussionmentioning
confidence: 61%
“…We also coded marijuana-themed images for product reference, where a code of 1 indicated that a Swisher wrapper was visible in the image (eg, a wrapper from a Swisher package was next to a hollowed-out cigar) and a code of 0 indicated that a Swisher wrapper was not visible anywhere in the image. In line with prior research using Instagram data to study tobacco-related behavior [ 10 ], we determined the presence (coded 1) or absence (coded 0) of alcohol in all images. One investigator coded all posts and another investigator coded a subsample of posts (n=200) to determine reliability.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…for exploring emerging health behaviors and sources of informational exposure (Allem, Chu, Cruz, & Unger, 2017;Ben Taleb, Laestadius, Asfar, Primack, & Maziak, 2018). Instagram users are a diverse cross-section of the population, including adolescents ages 13 to 17 years (Greenwood, Perrin, & Duggan, 2016) and parents/caregivers (Duggan, Lenhart, Lampe, & Ellison, 2015).…”
mentioning
confidence: 99%
“…Here we apply a simple MLP which only has one hidden layer [38]. In this analysis, we used the rectified linear unit (ReLU) activation function defined by [40]:…”
Section: Machine Learning Modelsmentioning
confidence: 99%